ADTH-01 Endoscopic full thickness resection in the colon: 3-year multicentre UK experience. (8th June 2018) - Hu, Max; Rahman, Imdadur; Ishaq, Sauid; Bhandari, Pradeep; Pugh, Stirling; Green, Susi; Suzuki, Noriko; Hopper, Andrew; Martin, John; Thomas-Gibson, Siwan; Patel, Praful; Boger, Phil
Abstract : Introduction: Endoscopic full thickness resection (eFTR) of the colon using the full thickness resection device (FTRD) is a novel method for removing lesions involving, or tethered to, deeper layers of the colonic wall. The UK FTRD registry collects data from multiple centres performing this procedure. We describe the feasibility and early outcomes of this technique. Methods: Registry data from April 2015 – January 2018 was analysed. Main outcome measures were technical success, procedural time, specimen size, R0 resection, endoscopic clearance, and adverse events. Reported technical difficulties were collated. Results: 38 cases were performed across 8 centres (median 2 cases per centre, range 1–23). Mean patient age was 70 years (39–93). Indications for eFTR include non-lifting adenoma (18 cases), T1 tumour resection (10), submucosal tumour (7), and appendix base adenoma (3). In 97.4% (37/38) of patients the lesion was reached with the FTRD. One caecal lesion could not be reached due to sigmoid diverticulosis. The procedure was technically successful in 91.9% of patients (34/37). Median procedure time was 41 minutes (11–86), median resection time 6 minutes (2–36), and median specimen size 22mm (10–30). R0 resection was achieved in 76.5% of patients (26/34). R0 resection was not achieved in 8 patients, of which 5 had no residual lesion on follow up, giving a total endoscopic clearance rate of 91.2% (31/34). Technical difficulty occurred in 9 patients; 6 due to snare failure and 3 due to lesion slippage on clip deployment. Of these 9 cases, 7 achieved R0 resection by use of further snare. Of the 2 patients with R1 resection, one has had follow up at 4 months with no evidence of residual lesion. Resection was unsuccessful in 3 patients; 2 due to significant tethering restricting lesion capture, and one due to haemodynamic instability from atrial fibrillation whilst pulling lesion into cap. Complications occurred in 2 patients; one acute appendicitis at day 6 after resection of appendix base adenoma, and one with mild asymptomatic stricture at eFTR site at follow up. There were no cases of bleeding, perforation, or fistula. Conclusions: eFTR has a high success rate in treating lesions not previously amenable to endoscopic therapy. Whilst technical difficulties may arise; complication rates are low and outcomes acceptable, making eFTR a viable alternative to surgery.